1995
DOI: 10.1007/bf00130360
|View full text |Cite
|
Sign up to set email alerts
|

Production of poly-?-hydroxybutyrate by Alcaligenes eutrophus transformants harbouring cloned phbCAB genes

Abstract: Three transformants of Afcufigenes eufrophus harbouring the recombinant plasmids containing phbCAE3, phbAE3, and phbC genes, were cultivated to investigate the effect of cloned genes on cell growth and poly-B-hydroxybutyrate accumulation. Both in the nutrient-rich and minimal media, the increased PUB accumulation in the transformants was observed compared to the parent strain, and this was the result of the increased enzyme activities in the transformants. Low carbon concentration and high C/N molar ratio favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Using transformed R. eutropha strains where either the PHB synthase or the PhbA ;-ketothiolase and acetoacetylCoA reductase had been overexpressed, these investigators found that enhanced levels of PHB synthase signifi cantly increased the molar fractions of 3HV and 4HB under conditions where P(3HB-3HV) and P(3HB-4HB) were produced. Park et al (1995cPark et al ( , 1997 reported that PHB synthase was the main controlling enzyme for PHB production in transformed R. eutropha strains. This differs somewhat with our predictions for plant production under dark conditions, but from the flux control coefficients calculated under light conditions, it is quite evident that about 400 of the control lies with PHB synthase.…”
Section: Resultsmentioning
confidence: 98%
“…Using transformed R. eutropha strains where either the PHB synthase or the PhbA ;-ketothiolase and acetoacetylCoA reductase had been overexpressed, these investigators found that enhanced levels of PHB synthase signifi cantly increased the molar fractions of 3HV and 4HB under conditions where P(3HB-3HV) and P(3HB-4HB) were produced. Park et al (1995cPark et al ( , 1997 reported that PHB synthase was the main controlling enzyme for PHB production in transformed R. eutropha strains. This differs somewhat with our predictions for plant production under dark conditions, but from the flux control coefficients calculated under light conditions, it is quite evident that about 400 of the control lies with PHB synthase.…”
Section: Resultsmentioning
confidence: 98%
“…The small arrowheads denote an internal standard, the protein tropomyosin (MW, 33,000; pI 5.2). (25), so cobalt was added to the glucose feed. During the initial induction phase, the phosphate concentration rapidly decreased in the reactor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli strains were grown in Luria-Bertani medium. R. eutropha strains were cultivated in one of the following media depending on the application: NR medium (36), PCT medium (Table 2), and Lee medium (25). NR is a complex medium, while both PCT and Lee media are minimal media.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the key enzymes of PHA biosynthesis (PHA synthases) are well known for their low substrate specificity, which is responsible for the large number of different PHA constituents found in microbial PHAs (59). As in the case of PHB synthases, different PHA synthases were cloned and expressed in various prokaryotic organisms (46,47,55,58,67); eukaryotic organisms, such as Saccharomyces cerevisiae (40); insect cells (73); and plants (21,48,53). Recently, the range of polymers synthesized by PHA synthases was extended to polythioesters consisting of 3-mercaptoalkanoates by employing PHA-accumulating bacteria, such as Cupriavidus necator (formerly Ralstonia eutropha), which typically accumulate PHB and other short-chain-length PHA, or engineered Escherichia coli strains and various organic thiochemicals as precursor substrates (42,43).…”
mentioning
confidence: 99%